Kinetics and performance of sewage sludge treatment using liquid state bioconversion in continuous bioreactor - A. Rahman, Roshanida (2009)
Liquid state bioconversion (LSB), a novel biodegradation, bioseparation, biosolids accumulation and biodewatering process was applied for sewage sludge treatment. The LSB process has been proven to be non hazardous, safe and environmentally friendly method for ultimate sludge management and disposal. The study was developed by using mixed fungi of Aspergillus niger and Penicillium corylophilum to treat sewage sludge in a LSB bioreactor. Results of the LSB process performance in previous studies were excellent; however the studies were only conducted on a batch system. The shortfall of the LSB batch process was identified when the LSB process was about to be applied in an actual wastewater treatment plant. The continuous process is an alternative treatment to be applied due to its advantages to handle continuous sewage sludge in the wastewater treatment plant. Therefore, this research was conducted in order to study the LSB process on the continuous system in terms of kinetic coefficients determination, process performance and process ptimisation. For the continuous LSB process, a mathematical model was developed from the basic principles of material balance based on Monod equation. By investigating the kinetics of substrate utilisation and biomass growth, the kinetic coefficients of Y, Kd, Ks and μmax were found to be 0.79 g VSS g COD-1, 0.012 day-1, 1.78 g COD L-1 and 0.357 day-1, respectively. In addition, the LSB performance was analysed by employment of the adapted fungi on a continuous basis to evaluate the bioconversion performance, bioseparation and dewaterability characteristics of sewage sludge at different hydraulic retention times (HRTs). The evaluation of the performance of LSB continuous process showed an improvement in the percentage of MLSS (mixed liquor suspended solids), COD (chemical oxygen demand), turbidity and protein in supernatant from 87 to 98%, 70 to 93%, 97 to 99% and 44 to 82%, respectively compared to the untreated sludge. The characteristics of the treated sludge from LSB continuous process in terms of settleability and dewaterability showed that the process was highly influenced by fungi entrapment with an increase of biosolids accumulation at 80% and filterability improved from 76 to 97%. The sludge volume index (SVI) in the range of 34 to 43 obtained from the treated sludge showed a good indicator of compressibility and settleability of the sludge. The LSB continuous process was modelled and analysed using response surface methodology (RSM) for optimisation purposes. Two operating factors namely HRTs and substrate influent concentrations (S0) were optimised in terms of sewage sludge dewaterability. The optimisation result showed that the optimum values were obtained at 3.62 days and 10.12 g L-1 of HRT and S0, respectively. The results were verified at a pilot scale bioreactor using the data obtained from the optimisation process. The final biosolids accumulation of 6% (w/w) obtained from the initial ~1% (w/w) of the untreated sludge shows that the LSB continuous process enhanced the dewaterability and hence, provide better waste management.